EFFECTS OF STUDENT-LED CLASSROOMS ON UZBEK EDUCATION - Uzoqova Marjona Sherali qizi (European Science Publishing, 2024)
This study investigates the effects of student-led classrooms on the educational outcomes in Uzbekistan. Employing a mixed-methods approach, we analyze quantitative data from standardized test scores and qualitative data from student and teacher interviews. Findings indicate significant improvements in student engagement, critical thinking skills, and teacher-student relationships. However, challenges such as the need for teacher training and resource availability persist. Our results suggest that while student-led classrooms offer substantial benefits, careful implementation is crucial for maximizing their effectiveness.
Keywords: Communicate, active role, critical thinking, teacher-centered methods, teacher-student dynamics, methodology, classrooms, education.